Foul Play in Sport as a Phenomenon Inconsistent with the Rules, yet Acceptable and Desirable: Ethical Conditions - Kosiewicz Jerzy (Sciendo, 2014)
The article has strictly a theoretical and non-empirical character. The author presents examples resulting from various observations. The aim of the paper is to present the causes, functions, and results of fouls, fouling, and foul play. Although fouls do not comply with the rules of games, the paper demonstrates that fouls are often used; they enjoy a quiet acceptance of the sporting world; they are tolerated and accepted; even more, they are often - more or less explicitly - desirable.